일품벼/모로베레칸 이입계통을 이용한 농업형질 관련 QTL 분석 - 구홍광(Hong-Guang Ju); 김동민(Dong-Min Kim); 강주원(Ju-Won Kang); 김명기(Myung-Ki Kim); 김연규(Yeon-Gyu Kim); 안상낙(Sang-Nag Ahn) (Korean journal of breeding, 2008)
We conducted a QTL analysis of agronomic traits using 117 BC3F5 and BC3F6 lines developed from a cross between Ilpumbyeo and Moroberekan. Genotypes of 117 BC3F5 lines were determined using 134 simple sequence repeat (SSR) markers. A total of 832 Moroberekan chromosome segments with 410 homozygous and 422 heterozygous, respectively, were detected, and the genetic distance of introgression segments ranged from 0.5 cm to 112.1 cm. A linkage map constructed using 134 SSR markers was employed to characterize quantitative trait loci (QTL). The 117 BC3F5 and BC3F6 lines were evaluated for seven agronomic traits at two locations in 2006 and 2007 and at one location in 2007. A total of 26 QTLs were identified for seven traits including days to heading, and the phenotypic variance explained by each QTL ranged from 9.2% to 24.2%. Moroberekan alleles contributed positive effects in the Ilpumbyeo background at eleven QTL loci including panicle length and spikelets per panicle. Five QTLs, two for days to heading and one each for culm length, panicle length and spikelets per panicle were consistently detected in every occasions indicating that these QTLs are stable. Among them, two QTLs, spp6 for spikelets per panicle and pl6 for paniclel length were localized in the similar region. Increase in spikelets per panicle at this locus might be due to the increase in panicle length, because both traits were associated with increase in spikelets per panicle and panicle length due to the presence of the Moroberekan allele. These Moroberekan QTLs might be useful in breeding programs to develop high-yielding cultivars.